2003
DOI: 10.1007/s00167-002-0322-y
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic mechanical stretching of human patellar tendon fibroblasts: activation of JNK and modulation of apoptosis

Abstract: Accelerated rehabilitation after tendon, ligament and bone injuries is widely accepted to avoid adverse effects of immobilization. However, progressive rehabilitation may also lead to an excessive inflammatory soft tissue response and often leads to structural and functional problems such as excessive scarring. The equivalent at the molecular/cellular level is in part the regulation of the sensitive homeostasis between proliferation and apoptosis. However, little attention has been paid to this aspect of tendo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
57
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 47 publications
(70 reference statements)
3
57
0
Order By: Relevance
“…The activation of the JNK signaling cascade generally results in apoptosis, although this pathway has also been shown to promote cell survival under specific conditions (25). In addition, the cyclic mechanical stretching of human patellar tendon fibroblasts activates JNK and modulates apoptosis (26). Although the effects of flavonoids on the NF-kB inflammatory pathway have received considerable attention, the expression of the inflammatory cytokine IL-6 is mediated by an activator protein-1 (AP-1) regulatory element in addition to NF-kB (27).…”
Section: Discussionmentioning
confidence: 99%
“…The activation of the JNK signaling cascade generally results in apoptosis, although this pathway has also been shown to promote cell survival under specific conditions (25). In addition, the cyclic mechanical stretching of human patellar tendon fibroblasts activates JNK and modulates apoptosis (26). Although the effects of flavonoids on the NF-kB inflammatory pathway have received considerable attention, the expression of the inflammatory cytokine IL-6 is mediated by an activator protein-1 (AP-1) regulatory element in addition to NF-kB (27).…”
Section: Discussionmentioning
confidence: 99%
“…These two pathways are associated with oxidative stress. Oxidative stress can be induced during high dose cyclic strain in human and animal tendon cells in vitro and in ex vivo [10,97,100]. Arnoczky et al [10] reported cyclical strain in cultured canine flexor tendon cells induces stress activated protein kinase, which in turn can induce apoptosis [100].…”
Section: Apoptosismentioning
confidence: 99%
“…Oxidative stress can be induced during high dose cyclic strain in human and animal tendon cells in vitro and in ex vivo [10,97,100]. Arnoczky et al [10] reported cyclical strain in cultured canine flexor tendon cells induces stress activated protein kinase, which in turn can induce apoptosis [100]. In a running rat supraspinatus tendon model, we also have found overuse induces upregulation of stress-related genes such as flice inhibitory protein (FLIP), heat shock protein 27 (HSP27) and testis heat shock-related protein 70 (HST70) [75].…”
Section: Apoptosismentioning
confidence: 99%
“…Yuan et al (2002) found that 13% of fibroblasts had undergone apoptosis in control sections of the subscapularis tendon. Apoptosis in radiofrequency-treated collagenous tissue at time 0 may occur due to ischemia, hypoxia, free radical generation, heat shock, physical damage or combinations of these factors (Jennings and Reimer 1991, Biagas 1999, Shackelford et al 2000, Skutek et al 2003. The onset of nuclear fragmentation is considered to be relatively short (1-3 h), but the exact onset of apoptosis after thermal treatment remains unclear (Gavrieli et al 1992, Smith et al 2000.…”
Section: Discussionmentioning
confidence: 99%
“…Although much research has been done, the loading conditions that are neces-sary to improve and accelerate the healing process without causing damage or adverse biomechanical effects remain unclear (Steadman et al 1989, Zeichen et al 2000, Bosch et al 2002, Skutek et al 2003.…”
mentioning
confidence: 99%